Development of Speaking Materials by Using Discussion Techniques at Muhammadiyah Vocational School 10 Kisaran - Nurman, Muhammad; Yulia Arfanti (PT Inovasi Pratama Internasional, 2023)
The objective of this research is to develop the English speaking materials for Vocational High School students based on discussion method at Muhammadiyah Vocational School 10 Kisaran. The data of this research are quantitative and qualitative. The researcher uses the percentage of the questionnaire of need analysis for the quantitative data. Meanwhile, for the qualitative, the researcher uses the content analysis for describing the data. The data is collected by using questionnaire and material (textbook). The result of needs analysis showed two parts, those were target needs and learning needs. After gathering the need analysis, the researcher formulated a course grid and wrote the first draft of the speaking materials. The speaking materials based on Project-Based learning contains of two units, those were: “Do You Agree with That? Giving Your Opinion” and “To Whom is the Letter Addressed?”. The researcher implemented ADDIE model for developing the materials. As the result, the researcher finds some error and lacks in the students’ text book. In order to maintain the students’ needs and the components of speaking, the researcher develop the material which has been verified by the expert. After getting the revision on the final product, the researcher finds that the materials can give the significant effect to the students’ speaking skills.